2010
DOI: 10.1108/17473611011093916
|View full text |Cite
|
Sign up to set email alerts
|

A study of financial awareness among youths

Abstract: Purpose -Credit card bankruptcies in Malaysia trebled from 2006 to 2007 and study loan defaults increased by 103 percent in the same period. In response to this, the paper aims to investigate the level of general financial and product awareness among young adults. The two research questions addressed are: how do demographic factors (age, gender and education level) influence the general financial awareness, and whether undertaking a business degree promotes greater financial and product awareness amongst youth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 40 publications
2
43
0
Order By: Relevance
“…Thus, it can be said that EPF investors in Malaysia are really concerned about Islamic and conventional unit trusts. Similar with the previous study done by Nga, Yong and Sellappan (2010) and Jonubi and Abad (2013), knowledge, financial literacy, and financial product consciousness are found important to influence people to make financial decision. Therefore, this research recommends that it is significant to increase financial knowledge among the public towards future financial preparation as well as to increase their standard of living.…”
supporting
confidence: 87%
“…Thus, it can be said that EPF investors in Malaysia are really concerned about Islamic and conventional unit trusts. Similar with the previous study done by Nga, Yong and Sellappan (2010) and Jonubi and Abad (2013), knowledge, financial literacy, and financial product consciousness are found important to influence people to make financial decision. Therefore, this research recommends that it is significant to increase financial knowledge among the public towards future financial preparation as well as to increase their standard of living.…”
supporting
confidence: 87%
“…Financial awareness is part of financial literacy and is an important factor that influences perceived knowledge which ultimately influences decision-making (Khan, 2015;Mason and Wilson, 2000;Priyadharshini, 2017). Nga et al (2010) provided evidence that financial awareness, that is, both general awareness and product awareness are affected by demographic factors. Khan (2015) indicated that financial awareness of financial products influences the financial decision.…”
Section: Financial Awarenessmentioning
confidence: 99%
“…While several studies suggest that gender may be related to young adults' financial behaviour, previous research results are mixed concerning the direction of the influence of gender on the quality of young adults' financial behaviour. While some research suggests that young males are more likely than young females to save a proportion of their income (Weekes, ) and that young males also have higher levels of financial awareness compared with young females (Nga et al ., ), other results indicate that women tend to be more risk adverse in financial choices than men (Dellande and Saporoschenko, ; Schurer, ), which may be positively related to information involvement (Chaudhuri, ).…”
Section: Conceptual Framework and Research Hypothesesmentioning
confidence: 99%